2021
DOI: 10.1038/s41598-021-01476-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring arterial tissue microstructural organization using non-Gaussian diffusion magnetic resonance schemes

Abstract: The purpose of this study was to characterize the alterations in microstructural organization of arterial tissue using higher-order diffusion magnetic resonance schemes. Three porcine carotid artery models namely; native, collagenase treated and decellularized, were used to estimate the contribution of collagen and smooth muscle cells (SMC) on diffusion signal attenuation using gaussian and non-gaussian schemes. The samples were imaged in a 7 T preclinical scanner. High spatial and angular resolution diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The FA is significantly lower in these aged samples than in previous studies investigating healthy porcine arterial tissue. 25–27 No subjects in this study died of cardiovascular disease; however, there were varying signs of atherosclerosis present for all subjects. While it is not possible to know for sure these subjects were asymptomatic, the signs of advanced disease present in most subjects combined with noncardiovascular-related CODs suggests it was in fact the silent progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The FA is significantly lower in these aged samples than in previous studies investigating healthy porcine arterial tissue. 25–27 No subjects in this study died of cardiovascular disease; however, there were varying signs of atherosclerosis present for all subjects. While it is not possible to know for sure these subjects were asymptomatic, the signs of advanced disease present in most subjects combined with noncardiovascular-related CODs suggests it was in fact the silent progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, the extreme scan times in this study are not clinically feasible; however, other studies have identified different DTI acquisition techniques which speed up acquisition. 26 , 27 , 29 While there is still work to be done on the clinical translation of this work, the authors think this study highlights the potential of this imaging technique for clinical use. Future work will focus on bringing this imaging method to more clinically relevant fresh tissue.…”
Section: Discussionmentioning
confidence: 85%
“…This relationship is further confirmed by the strong correlation between FA and cell density. While the mono-exponential DTI model has shown that the main contributor to the measurable anisotropic diffusion in arterial tissue is cellular content 52 , non-gaussian schemes, such as the stretched-exponential model, have been used to further hone in on alterations in the tissue microstructure 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Chemical exchange saturation transfer has shown an ability to measure specific concentrations of different molecules 69,70 ; however, its use in tissue engineering is limited 71 . DTI has been used in a handful of focused studies in different tissues to understand how different microstructural components affect the measurable signal 52,53,72 . A significant benefit to DTI is the ability to get directional information about the underlying microstructurea feature which is highly relevant in both cardiac 19,[73][74][75] and cartilaginous [76][77][78] tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation